Analisis Dan Rencana Perbaikan Proses Administrasi Operasional Menggunakan Business Process Model And Notation (Bpmn) Dengan Metode Business Process Improvement (Bpi) - Nabila Nuriyatul A’ini; Dwi Fatrianto Suyatno (CV. SINAR HOWUHOWU, 2026)
PT Sinar Harapan Mapan Santosa (SHMS) is a manpower outsourcing services provider managing approximately 200 to 250 daily workers. The current operational administration workflow (As-Is model) at PT SHMS faces conventional procedural obstacles, such as manual applicant data retrieval on HRD spreadsheets and parallel double-validation attendance between daily manual sheets and fingerprint machines. These upstream bottlenecks trigger excessive financial rework and delay the dispatch of hardcopy billing documents out of town, so that Service Purchase Order (SPO) issuance from the client's headquarters in Jakarta is delayed by 1 to 2 weeks, disrupting the company's operational cash flow. This study analyzes the root causes of these administrative issues and designs an improved workflow using Business Process Model and Notation (BPMN) combined with the Business Process Improvement (BPI) framework. This descriptive qualitative study evaluates data from 6 key process owners across core divisions through field observation, in-depth interviews, and time-analysis simulation in Bizagi Modeler. Root causes are dissected using the Ishikawa Diagram (Fishbone 4M+1E) and Non-Value-Added Analysis. The proposed workflow (To-Be Model) applies Harrington’s Streamlining Tools, comprising Simple Automated Systems via a cloud database, Bureaucracy Elimination and Error Proofing by removing manual paper attendance sheets, and a Paperless Environment alongside Bureaucracy Reduction through digital billing documents (e-documents). The simulation results indicate a significant reduction in average cycle time across all five administrative sub-processes: Sub-process 1 (Labor Request) was reduced to 2 hours 5 minutes (a 63.8% reduction); Sub-process 2 (Recruitment and Placement) to 6 hours 15 minutes (an 82.9% reduction); Sub-process 3 (Operational Coordination & Attendance) to 1 day 1 hour 46 minutes (a 75.2% reduction); Sub-process 4 (Labor Payroll) to 3 hours 23 minutes (a 91.6% reduction); and Sub-process 5 (Billing and Payment) to 8 days 1 hour 6 minutes (a 46.9% reduction). This upstream acceleration expedites the external bureaucratic verification of SPO issuance from Jakarta, thereby securing the company’s operational cash flow stability.